Sandstones modified with silico-organic compounds and changes of their porosity and flexural strength under concentrated load - REMBIŚ, Marek (Geology, Geophysics and Environment, 2010)
The sandstone samples representing 24 deposits localized in various geological regions of Poland were impregnated with liquid polymers, in which esters of the orthosilicic acid are active agents. Such preparations are commonly applied as stone strengtheners in conservation practices. The products of condensation of these polymers formed in the course of seasoning of the impregnated stone samples for 4 weeks have developed diversified microstructures. Their presence has lowered the porosity of the sandstones and changed the structure of the rock pore spaces. As a result, the sandstones have been strengthened as indicated by their values of the flexural strength under concentrated load. A distinct change of this parameter should be linked to exceeding of the threshold value of tetraetoxysilan oligomers concentration (percolation threshold) in the sandstones in question, mainly in their Liassic, Cretaceous and Istebna varieties. It has taken place in the samples with the porosity lowered at 41-66%. The percolation threshold has not been achieved in this part of the impregnated Magura, Krosno and Godula sandstones, in which their porosity has decreased at the value not exceeding 10%. In these cases, the value of the flexural strength under concentrated load remains at the same level as it was measured prior to impregnation.